Gliptin-associated Bullous Pemphigoid and the Expression of Dipeptidyl Peptidase-4/CD26 in Bullous Pemphigoid - Lindgren O; Varpuluoma O; Tuusa J; Ilonen J; Huilaja L; Kokkonen N; Tasanen K (ACTA DERMATO-VENEREOLOGICA, 2025)
Dipeptidyl peptidase-4 inhibitors (DPP-4i or gliptins) increase the risk of developing bullous pemphigoid. To clarify, whether gliptin-associated bullous pemphigoid has special features, we analyzed the clinical, histopathological and immunological features of 27 bullous pemphigoid patients, 10 of which previously used gliptin medication. Compared to those who had not previously received gliptins, subjects who had, showed higher BP180-NC16A ELISA (enzyme-linked immunosorbent assay) values, fewer neurological co-morbidities and shorter time to remission, but differences were not statistically significant. The HLA-DQB1* 03: 01 allele was more commonly present among the bullous pemphigoid patients than the control population, but was not more common in those with gliptin history. To determine the effect of gliptins on the expression of the DPP-4/CD-26 protein we performed immunohistochemistry, which showed that the skin expression of DPP-4/CD-26 was increased in bullous pemphigoid patients, but not affected by prior gliptin treatment. We conclude that DPP-4i medication is common among bullous pemphigoid patients and prior gliptin treatment may be associated with some specific features.